Génération automatique de maquettes de paysages grâce à l’open data - Maëlle Proust; Olivier Donzé; Kenzo Picenni; Anne Barrioz (Projets de Paysage)
The current profusion of geographic data, namely in open data format, is a tremendous opportunity for all those involved in spatial planning. However, their abundance, the heterogeneity of download sites, and the diversity of formats can complicate the use of such data. What's more, 3D representation of space is particularly time-consuming and requires specialised skills. These repetitive tasks are particularly well suited to automated programming. This is precisely what has been developed by the applied research group in Computer Landscape Modelling (MIP) at the Geneva School of Landscape, Engineering and Architecture (HEPIA). It has acquired cutting-edge skills and created open-source tools (plugins) to facilitate the automatic generation of 3D digital models of space. Maëlle Proust experimented with the application of these digital tools to the field of applied research on the ground as part of her master's thesis in spatial planning, with a focus on landscape architecture. Starting from the observation that the ground is not represented in urban planning, part of this work focused on how to make invisible living landscapes perceptible.